2020
DOI: 10.1021/acs.nanolett.0c02192
|View full text |Cite
|
Sign up to set email alerts
|

Spin Wave Radiation by a Topological Charge Dipole

Abstract: The use of spin waves (SWs) as data carriers in spintronic and magnonic logic devices offers operation at low power consumption, free of Joule heating. Nevertheless, the controlled emission and propagation of SWs in magnetic materials remains a significant challenge. Here, we propose that skyrmion-antiskyrmion bilayers form topological charge dipoles and act as efficient sub-100 nm SW emitters when excited by in-plane ac magnetic fields. The propagating SWs have a preferred radiation direction, with clear dipo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 53 publications
2
8
0
Order By: Relevance
“…1(c) with the contrast enhanced. The emission of spin waves by the skyrmion has a roughly circular symmetry, although around the skyrmion it can be seen that the spin wave is emitted as a spiral, similar to that seen in simulations of bilayer skyrmions 34 . For skyrmions with extended cores it has previously been shown that the excitation of the reversed magnetization of the core can produce spin waves 34,35 .…”
Section: Introductionsupporting
confidence: 73%
“…1(c) with the contrast enhanced. The emission of spin waves by the skyrmion has a roughly circular symmetry, although around the skyrmion it can be seen that the spin wave is emitted as a spiral, similar to that seen in simulations of bilayer skyrmions 34 . For skyrmions with extended cores it has previously been shown that the excitation of the reversed magnetization of the core can produce spin waves 34,35 .…”
Section: Introductionsupporting
confidence: 73%
“…For example, the counterclockwise (CCW) and clockwise (CW) modes possess M 𝑥 and M 𝑦 , while the breathing mode possesses M 𝑧 , which was confirmed by the selection rule for the microwave spectroscopy [45,[56][57][58]. In addition to these magnetically active modes, SkXs support polygon deformation modes, arising from singleskyrmion bound states [27][28][29][30]. These modes are characterized by azimuthal quantum number ℓ [59], with ℓ = 2 for elliptic, ℓ = 3 for triangle, ℓ = 4 for square, ℓ = 5 for pentagon, and ℓ = 6 for hexagon, showing higher multipolar characters.…”
Section: B Skyrmion Crystal Phasementioning
confidence: 72%
“…According to previous studies, most of the bound states of a single skyrmion are found above the bulk continuum excitations of the ferromagnetic background [27,28,30]. To eliminate the bulk continuum from the low-energy spectrum, we introduce a magnetic field potential trap [see Fig.…”
Section: Appendix E: Hybridization Of Single-skyrmion Bound Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, Di ́az et al found that the interlayer exchange coupled skyrmion−antiskyrmion pair can serve as a spin-wave antenna, while such a system cannot sustain long-distance spin wave propagation. 48 In this work, we study the chiral emission of exchange spin waves by magnetic skyrmions using micromagnetic modeling. 49 A hybrid magnetic double layer system is investigated, where an ultrathin ferromagnetic metallic layer with interfacial DMI is on top and a magnetic thin-film insulator is on bottom.…”
mentioning
confidence: 99%